A European emotional investigation in the field of shoe design. (29th December 2008) - Bouchard, Carole; Mantelet, Fabrice; Aoussat, Ameziane; Solves, Clara; Gonzalez, Juan; Pearce, Kim; Lottum, Carolyn; Coleman, Shirley
In this paper we report the results of a Kansei Engineering System study. A methodology for the application of Kansei Engineering at the European level has been developed and validated in the field of shoe design by means of the development of experimental studies in two different phases of product design: the information phase in the earliest stages of the design process and the generation and evaluation phase corresponding to the latest stages of the process.